Impact of host responses on control of hepatitis C virus infection in Chinese blood donors - Li, T; Chen, Z; Zeng, J; Zhang, J; Wang, W; Zhang, L; Zheng, X; Shuai, L; Klenerman, P; Allain, J; Li, C (2011)
A study was undertaken to explore the molecular mechanisms underlying control of HCV infection in blood donors in China. Factors including clinical information, anti-HCV reactivity (S/CO), IFN-α and IFN-γ, viral loads and genotypes were correlated with 160 index plasma samples at three statuses of 45 recovered, 76 chronic or 39 false positive anti-HCV reactive blood donors. The spontaneous recovery rate was 37.2%. Viral loads of 76 HCV plasmas ranged between 59.8IU/ml and 2.43×10 6IU/ml (median 3.67×10 4IU/ml). Genotypes 1, 2, 3 and 6 of 63 HCV strains were identified phylogenetically. Recovered donors were significantly younger (p=0.002) and had lower level IFN-γ (p=0.001) than chronically HCV infected donors. Circulating levels of IFN-α and IFN-γ were higher in those with low viral load and were low in middle or high viral load samples. The ratio of IFN-α to IFN-γ (IFN-α/γ) was significantly positively correlated with viral load (p=0.037), and viral load was inversely correlated with IFN-γ in chronic HCV infection regardless of genotype. The study revealed clearly different relationships between IFN-α and IFN-γ in relation to viral load in HCV. A novel measure of IFN-α/γ ratio could be a new approach to evaluate long term outcome of HCV infection. © 2011 Elsevier Inc.